Análise de indicadores de desempenho de projetos a partir de critérios de sucesso: o caso SEBRAE/RN - Silva, Alinne Priscilla Dantas (2014)
Today, organizations that operate with public funds have the challenge of communicating results that go beyond achieving goals, costs and deadlines. Notes the importance for organizations to have a system for evaluating projects with indicators that reflect their success or failure and thus may contribute to the operational strategy of the organization. The study comprises a theoretical and empirical analysis about the projects performance indicators and success criteria, directing the search to the Serviço de Apoio às Micro e Pequenas Empresas do Rio Grande do Norte - SEBRAE / RN, in order to analyse its projects performance indicators based on the evaluation of the success criteria. As theoretical framework, it was used the multiple dimensions of successful projects proposed by Shenhar and Dvir (2007), and as the analysis of performance indicators was based on the methodology proposed by Barclay; Osei-Bryson (2010). To achieve the objectives of this study, a survey of exploratory and descriptive nature was carried out through a case study, with mixed approach, using quantitative and qualitative methods. The study approached six (6) projects of the organization and applied information collection typed “survey” with the target audience of the projects, their managers and partners, team management and project monitoring and executive board of the organization. The qualitative research was addressed to the results analyzes, evaluation of existing criteria for success in the organization, its system of project evaluation and project indicators. After analyzing the research, it is noted the high concordance of answered as the five (5) dimensions of success criteria proposed by Shenhar and Dvir (2007). It is stated that the organization has a formal process for measuring and evaluating their projects, according to outcome indicators of cost, time, organizational image, satisfaction, applicability, sales, productivity, market competitiveness and thus there is a gap between theory of success criteria Shenhar and Dvir (2007) and the existing practice in the organization. After study of bibliographic references and data analysis, it is observed that the performance indicators of the organization are aligned the definition of Barclay and Osei- Bryson (2010). It is suggested to SEBRAE / RN, which in its evaluation of projects, the success criteria for projects contemplated in Shenhar and Dvir theory (2007) are analyzed and they are transformed into a tool for measuring the success or failure of projects.